Avances en la lucha contra la desigualdad y la violencia por razón de género en el ámbito laboral - Quiñones Infante, Sergio (2019)
The purpose of this article is to assess the main progress that the peruvian state has made in preventing and eradicating gender-based inequality and violence in the workplace, given that in our country both phenomena constitute very serious problems that must be fought decisively and frontally. It is not, therefore, a task in which our country is alone; on the contrary, it is a global challenge with which we all aspire to live in a more equal and safer world. The big objective in this area by 2021 should be to become a bicentennial country in which wage gaps have been substantially narrowed, where women have full equal opportunities and live free from violence, within the framework of the implementation of public policies to promote gender equality and the empowerment of all women at all levels.